Perancangan Aplikasi Web Manajemen Tamu dan Visitor Pass Digital pada Apartemen Eksekutif Menteng - I Gusti Agung Ayu Anindya Bulan Shintania Kamasan; Syafrianto Syafrianto (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2026)
The development of information technology demands greater efficiency and security in guest management, especially in high-density residential environments like apartments. This study aims to address the security risks and administrative inefficiencies at Executive Menteng Apartment, where guest recording is still performed manually using physical logbooks. This manual system is prone to data loss, reporting delays, and lack of visitor validation. To solve this, a web-based guest management application featuring a digital visitor pass with QR Code was designed. The development methodology followed the Waterfall model, comprising analysis, design, implementation, testing, and maintenance phases. The research results in a functional web application that automates guest recording in real-time and generates unique QR Codes for visitor validation. System validation was conducted using black-box testing, which confirmed that all features, including multi-role login and report generation, operate correctly. This digital transformation reduces paper usage and significantly enhances the security monitoring of visitors, providing the management with accurate and accessible data.